Temperature Monitoring and Forecast System in Remote Areas with 4.0G LTE Mobile Technologies - Kevin Alexandre Riaño Vargas; Octavio José Salcedo Parra; Miguel J. Espitia R. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The need to monitor areas of high risk in terms of temperature indexes has included two important elements for its compliance: monitoring and forecast of records in an environment. Performing this procedure manually is inefficient as it provides a flat perspective and can’t predict the state of the environment with rigor. Software systems are contemporary elements in constant refinement, which satisfy emerging needs of a context, so that, in relation to monitoring and forecast an environment, it allows a sophisticated automation of the process, and that tends to lead to a better supervision of the risks in the environment. This article presents a proposal for the supervision of high-risk areas, through temperature registers, manageable through the design of a software system with the implementation of mobile 4.0G LTE technologies, aimed at efficiency and effectiveness in the notification of environmental status. Finally, I conclude with a remote temperature monitoring and forecast system, using mobile technologies, with a fuzzy logic prediction system with a quadratic error not greater than 2.6%, that is, on a fuzzy algebra system whose Numerical calculation does not exceed this error value in comparison with actual values; At the same time that the future works are presented from the approach of the research that is postulated, according to the emergence of new perspectives related to this developing software system.